Political economy of tobacco control in low-income and middle-income countries: lessons from Thailand and Zimbabwe (The World Health Organization, 2000)
Crucial to the success of the proposed Framework Convention on Tobacco Control will be an understanding of the political and economic context for tobacco control policies, particularly in low-income and middle-income countries. Policy studies in Thailand and Zimbabwe employed the analytical perspective of political economy and a research strategy that used political mapping, a technique for characterizing and evaluating the political environment surrounding a policy issue, and stakeholder analysis, which seeks to identify key actors and to determine their capacity to shape policy outcomes. These policy studies clearly revealed how tobacco control in low-income and middle-income countries is also being shaped by developments in the global and regional political economy. Hence efforts to strengthen national control policies need to be set within the context of globalization and the international context. Besides the transnational tobacco companies, international tobacco groups and foreign governments, international agencies and nongovernmental organizations are also playing influential roles. It cannot be assumed, therefore, that the tobacco control strategies being implemented in industrialized countries will be just as effective and appropriate when implemented in developing countries. There is an urgent need to expand the number of such tobacco policy studies, particularly in low-income and middle-income countries. Comprehensive guidelines for tobacco policy analysis and research are required to support this process, as is a broader international strategy to coordinate further tobacco policy research studies at country, regional and global levels.